Advancing Design Thinking Towards a Better Understanding of Self and Others - James, Meredith (FormAkademisk, 2017)
In advancing the design discipline, two key themes repeatedly emerge: design's move away from materialism and augmenting better problem-solving skills through self-awareness. The first anchors design in a process rather than a product, something that is native to the concept of design thinking. The second anchors the designer in ethics. Designers who have a strong sense of self-awareness, understanding their own roles, biases and influences and the larger contexts they inhabit, are overall better equipped to solve problems. If we continue to advance design away from materialism and towards self-awareness, what models can we follow in this change?